Non-Fungible Token as a Condition for Intellectual Property Registration and Digital Asset Marketing Strategy Using Digital Tokens - Shelly Kurniawan; Demson Tiopan (Politeknik Siber Cerdika Internasional, 2023)
Creativity is unlimited. Creativity is not only visible in real terms that can be touched by human hands, but now it is widespread in cyberspace. This creativity can be in the form of music, inventions, logos, and others that can be protected by intellectual property. The protection of intellectual property can be combined with a Non-Fungible Token. The purpose of this research is to examine the use of Non-Fungible Tokens as an intellectual property registration and the use of Non-Fungible Token as a marketing strategy for digital assets. The research method is normative juridical which will multiply from some secondary literature, books, journals, and other sources related to intellectual property, Non-Fungible Tokens, and marketing strategies. The use of Non-Fungible Tokens as a condition for intellectual property registration can have a positive impact, especially in terms of determining novelty requirements. Businesses can use Non-Fungible Tokens as a marketing strategy to market their works or digital assets.